Impact of prior immunotherapy on paclitaxel/bevacizumab in advanced non-squamous non-small cell lung cancer - Peyret, Agathe; Le Berrurier, Clémentine; Heraudet, Luc; Delon, Tara; Zysman, Maéva; Larroquette, Mathieu; Leroy, Laura; Cousin, Sophie; Domblides, Charlotte (Frontiers in Oncology, 2025)
Immunotherapy is becoming essential in the management of advanced non-small cell lung cancer (NSCLC); however, the best treatment sequence remains to be determined. Some data suggest that immunotherapy prior to chemotherapy with paclitaxel/bevacizumab (PB) appears to be an interesting option. Here, we study this sequence in a validation cohort from the Bordeaux Cancer Institute (France). We retrospectively included all patients with NSCLC diagnosed between 2015 and 2021, treated with PB directly after immunotherapy (CAI) or without prior exposure to immunotherapy (CWPI). The primary outcome was the time to treatment discontinuation (TTD), and the secondary endpoints were progression-free survival (PFS), overall survival (OS), overall response rate (ORR), and disease control rate (DCR). We included 121 patients: 60 in the CAI group and 61 in the CWPI group. Their characteristics were comparable, even for the main prognostic criteria. The median number of lines received was higher in the CAI group (4 vs. 2). There was a significant difference in TTD (HR = 0.55, 95% CI 0.34–0.72, p = 0.0002), PFS (HR = 0.60, 95% CI 0.41–0.87, p < 0.005), and ORR (58% versus 38%, p < 0.05) between the two groups, as well as a non-statistically significant trend toward better OS (7.40 vs. 3.70 months, HR = 0.76, 95% CI 0.52–1.10, p = 0.15). We found a significant difference in TTD, PFS, and ORR for PB after exposure to immunotherapy, with a trend toward better OS. This suggests that sequential treatment with immunotherapy followed by chemotherapy could be an interesting option after first-line treatment.